DOPPLER INDICES OF FETAL MIDDLE-CEREBRAL AND UMBILICAL ARTERIES IN NORMAL 28–40 WEEKS PREGNANCIES - SUMAN, ANJALI; JENY, MISS; KUMAR, SANTOSH; BHARTI, SUBHRA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The aim of the study was to establish normative data for the pulsatility index (PI), resistive index, and cerebro placental ratio of umbilical artery (UA), and fetal middle cerebral artery (MCA) of Indian pregnant women in the third trimester of pregnancy using multiples of the median and percentile reference range. Methods: It was a cross-sectional study; the study was carried out at the Department of Obstetrics and Gynaecology and Radiology in MGM Medical College and LSK Hospital, the tertiary care and teaching hospital. A total of 200 cases were enrolled for this study. Patients with Singleton low-risk pregnancies with confirmed gestational age, normal anatomy, normal estimated fetal weight, and born at term with birth weight between 10th and 90th percentile and gestational age was based on LMP date, corrected if required by trimester first/second (Before 20 weeks) fetal sonographic parameters were included in the study. Results: We found from 28 weeks to 39 weeks of gestational age, MCA PI showed a significantly positive correlation with the cerebro-placental ratio (CPR) 40th week of gestational age. We found no significant correlation. While from 28 weeks to 40 weeks of gestational age, UA PI showed a significantly negative correlation with the CPR. Conclusion: Doppler ultrasound is used as a part of the clinical protocol in the surveillance of pregnancies. The UA and MCA Doppler indices and CPR are currently used to modify the scheduling of antepartum surveillance and, in some cases, to timely delivery of the compromised fetus. Researchers measured the pulsatility, resistivity, and cardiac indices of the UA and the fetal MCA between 28 and 40 weeks of gestation to establish a normal range.